Effects of Chloride, Sulfate and Magnesium Ions on the Biomineralization of Calcium Carbonate Induced by Lysinibacillus xylanilyticus DB1-12. Issue 10 (1st November 2022) - Yan, Huaxiao; Huang, Meiyu; Wang, Tiantian; Xu, Yudong; Meng, Long; Zhao, Lanmei; Han, Zuozhen; Wang, Jihan; Tucker, Maurice E.; Zhao, Hui
Abstract: Microbially-induced calcium carbonate precipitation (MICP) has been studied extensively. However, the effect of different sources of magnesium ions on calcium carbonate biomineralization has rarely been examined. In this study, Lysinibacillus xylanilyticus DB1-12 bacteria isolated from petroleum samples were used to biomineralize calcium ions under the action of different sources of magnesium (magnesium chloride and magnesium sulfate). The results show that calcium ion precipitation ratios were much higher in MgSO4 group experiments than in the MgCl2 group ( p  < 0.01). The mineral phases in the MgCl2 group experiments were the same as those in MgSO4 group at each Mg/Ca ratio. Minerals with a 'twisted' shape were much more common in the MgSO4 group; the protein secondary structures hidden in minerals were much more abundant in the MgCl2 group, and the activation energy of biotic monohydrocalcite at a Mg/Ca ratio of 11 was also much higher in the MgCl2 group than in the MgSO4 group. The main reasons for these differences are closely related to the lower magnesium content and the more common protein secondary structures in the monohydrocalcite in the MgCl2 group. The shift of Mg1s XPS spectra suggests that the chemical interactions occurring on the monohydrocalcite surfaces in the MgCl2 group were different from those in the MgSO4 group. The δ 13 CPDB values of the biominerals in the MgSO4 group are in the range of −16.93 to −18.87‰, lower than those in the MgCl2 group (-15.77 to −18.69‰). The morphology of L. xylanilyticus DB1-12 became deformed and some rod-shaped protrusions developed on the cell surface during the process of biomineralization. This study not only contributes to the understanding of biomineralization mechanisms generally, but is also helpful in the interpretations of paleo-environmental conditions.